The role of the gut microbiota in pathogenesis and treatment of depression - Klaudia Bogusz; Natalia Baran; Marcela Maksymowicz; Adriana Bielak; Aleksandra Nowak; Łucja Cywka; Weronika Szwed; Alicja Nowak; Piotr Machowiec (Kazimierz Wielki University, 2023)
Introduction and purpose Depression is the most common mental disorder, but the exact mechanisms underlying the pathophysiology of depression remain unknown. Abundant research evidence suggests that changes in the gut microbiota play a key role in the pathophysiology of depression through the brain-gut-microbiota axis. The aim of this study was to present the current state of knowledge on the role of gut microbiota in pathogenesis and treatment of depression and discuss its potential as a therapeutic target for depression A brief description of the state of knowledge The digestive tract and the processes which are set in it as well as the inhabitting microorganisms have a significant impact on our mental health and mood. The scientific research repeatidly confirm a strict relationship between the digestive and nervous systems. A microbiome-based approach is becoming increasingly prevalent in the understanding and treatment of neuropsychiatric disorders, especially depression. Antidepressants which are today the first-line therapy in the treatment of this disease are based inter alia on the antimicrobial and immunomodulatory mechanism of action. Conclusion  Immune cells which are settled in the intestines affect not only our physical health but also the mental one. Due to the relationship between depression and the gut microbiota, we have many treatment options that involve direct modification of the composition of the microbiome which include prebiotics, probiotics (psychobiotics) and faecal microbiome transplantation.